Pengaruh Citra Merek dan Promosi terhadap Keputusan Pembelian Konsumen pada Sirempah di Kota Jambi - R, Mardiana; Kadar, Melani (Jurnal Ilmiah Manajemen dan Kewirausahaan (JUMANAGE), 2026)
This study aims to analyze the influence of brand image and promotion on consumer purchasing decisions at the Sirempah MSME in Jambi City. Sirempah is a modern herbal medicine business challenges facing in building an effective brand image and promotional strategies, especially among the younger generation. A total of 150 respondents who were Sirempah customers were given a questionnaire as part of the quantitative survey methodology of this study. Sampling was carried out using a simple random sampling method. Multiple linear regression analysis was used to test the partial and simultaneous impact of the independent variables (promotion and brand image) on the dependent variable (purchase choice). The study findings indicate that, both partially and simultaneously, customer purchasing decisions are positively and significantly influenced by brand image and marketing. These results imply that to increase consumer appeal and loyalty in an increasingly competitive market, Sirempah must strengthen its brand strategy and improve the quality of its promotions. Keywords : Consumer Purchase Decision, Brand Image, Promotion.